Degradation of rRNA in Salmonella strains: a novel mechanism to regulate the concentrations of rRNA and ribosomes. - Hsu, D (1994)
We have previously shown that the 23S rRNA of Salmonella strains is highly fragmented by specific enzyme cleavages. In this article, we report that 23S rRNA of Salmonella strains is rapidly degraded as the cells enter the stationary phase. More than 90% of the 23S rRNA is degraded when the cells reach the stationary phase. The rate of degradation of 23S rRNA correlated with its degree of fragmentation. This degradation is probably mediated by newly synthesized protein factor(s), since treatment with chloramphenicol or rifampin inhibits the rRNA degradation. We propose that degradation of 23S rRNA is a novel mechanism in the regulation of the bacterial 23S rRNA and ribosome concentration and that this additional regulatory mechanism provides some selective advantage to cells.